Valence of Opinion: Keputusan Pembelian Produk Skintific pada Akun Instagram @skintificid - Sagala, Magdalena Tiur Romida; Abidin, Zainal; Rifai, Maulana (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of valence of opinion on Instagram social media on purchasing decisions for Skintific products. The research instrument used in this research used a questionnaire and used a Likert scale to answer statements. The population in this research are followers of the Instagram account @skintificid. The sample in this research were 100 respondents. The sampling technique uses a non-probability sampling technique with a purposive sampling method, with the criteria: 1) active followers of the @skintificid Instagram account, 2) have interacted with the comments column of the @skintificid Instagram account, 3) have purchased Skintific products at least once. Data collection techniques in research through questionnaires in the form of a Google Form. Data analysis techniques in this research used validity test, reliability test, normality test, coefficient of determination test, simple linear regression test, hypothesis test. The results of the research show that there is a significant influence on the valence of opinion on social media Instagram on purchasing decisions for Skintific products.